2013
DOI: 10.1371/journal.pone.0080732
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Function of the Ikaros Transcription Factor in Primary Leukemia Cells from Pediatric Newly Diagnosed High-Risk and Relapsed B-precursor ALL Patients

Abstract: We examined the constitutive function of the Ikaros (IK) transcription factor in blast cells from pediatric B-precursor acute lymphoblastic leukemia (BPL) patients using multiple assay platforms and bioinformatics tools. We found no evidence of diminished IK expression or function for primary cells from high-risk BPL patients including a Philadelphia chromosome (Ph)+ subset. Relapse clones as well as very aggressive in vivo clonogenic leukemic B-cell precursors isolated from spleens of xenografted NOD/SCID mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(42 reference statements)
2
5
0
Order By: Relevance
“…In this context, we suggest that the function of Ikaros was not affected by the expression of Ik6 and Ik8. This result is in accordance with data reported by other authors, who demonstrates that the function and expression of Ikaros were not decrease by IKZF1 deletions in ALL blasts [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this context, we suggest that the function of Ikaros was not affected by the expression of Ik6 and Ik8. This result is in accordance with data reported by other authors, who demonstrates that the function and expression of Ikaros were not decrease by IKZF1 deletions in ALL blasts [ 22 ].…”
Section: Discussionsupporting
confidence: 94%
“…The long isoforms (Ik1, Ik3A and Ik2) were expressed more frequently in our patients in contrast to other populations reported that express both short and long isoforms in B-ALL cases and only short isoforms in the T-ALL patients [ 6 ]. Much like other authors [ 6 , 20 22 ], we observed a great heterogeneity in the expression of all Ikaros transcripts in the ALL-children studied.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In an analysis of more than 250 BCR ‐ ABL1 ‐positive and ‐negative paediatric BCP ALL cases, neither intragenic IKZF1 deletions nor any expression patterns indicative of such deletions were observed (Qazi et al , ; Uckun et al , ). Furthermore, unaffected expression levels in cases with hemizygous IKZF1 deletions and low expression of IK6 in healthy controls have also been reported (Tokunaga et al , ; Volejnikova et al , ).…”
Section: Controversiesmentioning
confidence: 99%
“…We focused our analysis on mRNA expression comparing normal vs. ALL samples (log 2 median centered expression values for each data set) and filtered expression signals that were greater than 1.5-fold difference and P-value from two sample t-tests less than 0.001. In addition, we compiled 6 archived gene expression profiling datasets that measured expression from B-lineage ALL patients hybridized to Human Genome U133 Plus 2.0 Array, including GSE11877, n = 207; GSE13159, n = 823; GSE13351, n = 107; GSE18497, n = 82; GSE28460, n = 98; GSE7440, n = 99 (Total n = 1416), as described [28][29][30][31] .…”
Section: Gene Expression Analysesmentioning
confidence: 99%